Sporadic occurrence of H9N2 avian influenza infections in human in Anhui province, eastern China: A notable problem. (March 2020) - He, Jun; Wu, Qian; Yu, Jun-Ling; He, Lan; Sun, Yong; Shi, Yong-Lin; Chen, Qing-Qing; Ge, Ying-Lu; Zhang, Zhu-Hui; Li, Wei-Wei; Hou, Sai; Zhu, Meng; et al.
Abstract: H9N2 viruses can cause great economic losses to the domestic poultry industry when co-infected with other influenza viruses or pathogens. . To better understand the molecular characteristics of H9N2 avian influenza viruses (AIVs) and analyze the genetic evolutionary relationship, we isolated three H9N2 subtypes AIVs from nasopharyngeal swab specimens from the three cases reported in Anhui province since 2015, and systematically reviewed the genome-wide data of 21 poultry–isolated H9N2 viruses during 1998–2017. The six internal genes of three human-isolated viruses and recent poultry-isolated viruses (since 2014) in Anhui province presented high gene homologies with HPAI H7N9, even including H10N8 and H5N6. The three human-isolated H9N2 AIVs and poultry-isolated viruses (since 2008) in Anhui province were highly similar, and classified into genotype S. Seven N-linked potential glycosylation sites in the HA protein were detected in the three human-isolated viruses, which also appeared in poultry-isolated H9N2 AIVs. None of the human-isolated H9N2 AIVs had the I368V mutation in PB1 protein, but all the poultry-isolated H9N2 viruses in 2017 carried this mutation. Multidisciplinary, cross-regional and cross-sectoral approaches are warranted to address complex public health challenges and achieve the goal of 'one health'. Highlights: Influenza A (H9N2) viruses may undergo a period of adaptation through dynamic reassortment and pose a threat to mammals. Currently, the internal genes of H9N2 are similar to HPAI H7N9 and H10N8 that have not been found in Anhui province. Close attention should be paid to the evolutionary dynamics of the virus in poultry.